PERAN BPK DALAM PENGAWASAN PREVENTIF TERHADAP DANA KOPERASI MERAH PUTIH BERDASARKAN INPRES NOMOR 9 TAHUN 2025 - Mayolla Octavia; W Riawan Tjandra (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2025)
Research Objective: This article examines the accountability paradox of using public funds to finance community-based cooperatives in Indonesia. It focuses on the role and limitations of supreme audit institutions (SAIs), particularly the Audit Board of the Republic of Indonesia (BPK), in overseeing the Koperasi Merah Putih programme, as established by Presidential Instruction No. 9 of 2025. Research Method: The study uses a normative juridical approach, relying on constitutional analysis, legal interpretation, and comparative institutional analysis. It reviews Indonesia’s legal framework and compares it with similar programmes in India, the Philippines, Kenya, and Brazil. Results: The study finds BPK has clear constitutional authority under Article 23E of the 1945 Constitution and Law No. 15 of 2006 to audit state-funded cooperatives. However, this authority is weakened by the non-regulatory nature of presidential instructions and the lack of detailed technical accountability rules. Four main structural problems emerge: limited audit access to non-governmental entities, insufficient audit capacity compared to programme size, fragmented digital financial reporting, and independence pressures arising from high-profile political programmes. Findings and Implications: The accountability paradox shows a mismatch between public financial management systems and the decentralized nature of cooperatives. This challenge is not unique to Indonesia but is shared by SAIs across the Global South. Conclusion: Solving the accountability paradox requires reforms beyond BPK’s capacity, including new technical regulations, stronger inter-agency supervision, and integration of e-audit systems for cooperative financial reporting. Contribution: The article introduces the accountability paradox as a framework for SAI governance challenges in state-directed cooperative funding, and proposes a legally grounded reform agenda relevant to similar programmes globally. Limitations and Suggestions: As a normative study, it does not include field data. Future research should add qualitative fieldwork on BPK audit practices and village-level cooperative financial management to test and expand the proposed framework.